A Pyramidal Lattice Frame: Pathways to Inversion - Guan, Yue; Virgin, Lawrence N. (International journal of structural stability and dynamics, 2021)
This paper considers the load–deflection behavior of a pyramid-like, shallow lattice structure. It consists of four beams that join at a central apex and when subject to a lateral load, it exhibits a propensity to snap-through: a classical buckling phenomenon. Whether this structural inversion occurs, and the routes by which it happens, depends sensitively on geometry. Given the often sudden nature of the instability, the behavior is also examined within a dynamics context. The outcome of numerical simulations are favorably compared with experimental data extracted from the testing of three-dimensional (3D)-printed specimens. The key contributions of this paper are that despite the continuous nature of the physical system, its behavior (transient and equilibria) can be adequately described using a discrete model, and the paper also illustrates the utility of 3D-printing in an accessible research context.